PENGARUH PENAMBAHAN IKAN LELE (Clarias batrachus) PADA PEMBUATAN CENDOL TERHADAP TINGKAT KESUKAAN DAN KADAR PROTEIN - Feti Fatimatuzzahroh; Tabi’in; Novianti, Teni (LPPM UNU CIREBON, 2023)
Catfish (Clarias batrachus) is a type of freshwater cultured fish that is quite popular with the public. However, with the abundance of fishery products in Indonesia, it is inversely proportional to the consumption of protein in Indonesian people who do not meet the Adequacy of Nutrition Standards. Cendol is a typical Indonesian drink made from hunkwe flour with incomplete nutritional content. In order to increase the fish consumption of the Indonesian people, the authors are interested in conducting research on the addition of catfish (Clarias batrachus) animal protein to the manufacture of cendol and its effect on the panelist's preference level and protein content. This study aims to determine the effect of adding catfish (Clarias batrachus) to the production of cendol on the level of preference and protein content. The research method used was an experimental method with 30 panelists and 3 treatments, the percentage of catfish meat was 20%, 30%, 40%. The parameters observed were hedonic scale sensory tests and cendol protein levels with the addition of catfish. The results showed that the addition of catfish meat in the manufacture of cendol had an effect on aroma, taste and texture. The best cendol according to consumer acceptance based on sensory tests of color, aroma and taste parameters was in treatment A (addition of catfish meat percentage of 20%), while the best texture was in treatment B (addition of catfish meat percentage of 30%). The catfish cendol had the best protein content in treatment C (addition of 40% catfish meat) which was 1.53%.